Association of Fentanyl With Neurodevelopmental Outcomes in Very-Low-Birth-Weight Infants. (March 2014) - Lammers, Erin M.; Johnson, Peter N.; Ernst, Kimberly D.; Hagemann, Tracy M.; Lawrence, Shelley M.; Williams, Patricia K.; Anderson, Michael P.; Miller, Jamie L.
Background: Opioids are commonly used in the neonatal intensive care unit (NICU). Negative neurodevelopmental effects in the short-term setting have been associated with opioids ; however, long-term studies have been limited.Objective: The primary objective was to determine if there is a dose relationship between fentanyl and neurodevelopmental outcomes, as measured by Bayley Scales of Infant and Toddler Development (Bayley-III) composite scores for language, cognition, and motor skills. Secondary objectives included comparison of Bayley-III scores and neurodevelopmental impairment classification based on fentanyl exposure.Methods: A retrospective evaluation of 147 very-low-birth-weight infants with Bayley-III scores obtained at a chronological age of 6 months to 2 years at clinic follow-up was conducted. Univariate and multivariable linear regression analyses were used to determine if there was a dose-related association between fentanyl and neurodevelopmental outcomes. To evaluate secondary outcomes, patients were divided based on cumulative fentanyl dose ("high-dose" versus "low/no-dose").Results: The univariate analysis found a statistically significant decrease in cognition ( P = .034) and motor skills scores ( P = .006). No association was found in the multi-variable regression between fentanyl cumulative dose and Bayley-III scores. There was a significant decrease in the motor skills score between the high-dose versus low/no-dose group, 94 ± 20 versus 102 ± 15, respectively ( P = .026); however, no statistical differences were noted for language or cognition scores or neurological impairment classification.Conclusions: When controlling for other variables, the cumulative fentanyl dose did not correlate with neurodevelopmental outcomes. Further evaluation of benefits and risks of opioids in premature infants are needed.